Preparation and Performance of Asphalt Compound Modified with Waste Crumb Rubber and Waste Polyethylene - Yuqiao Yang; Youliang Cheng (Advances in Materials Science and Engineering)
Three kinds of modified asphalt were prepared by adding waste crumb rubber (WCR), waste polyethylene (WPE), and WCR/WPE to base asphalt, respectively. The influence of different doses on the performance of modified asphalt, such as 25°C penetration, softening point, 5°C ductility, and 135°C, 165°C viscosity, was studied, and the modification mechanism of modified asphalt was discussed through the fluorescence microscope. As the waterproofing materials, the waterproofness of WCR/WPE compound modified asphalt was tested. The results show that the WPE modified asphalt has excellent resistance to high temperature and WCR modified asphalt has good low temperature resistance. The resistance to deformation ability of WPE modified asphalt is better than that of the WCR modified asphalt. The 135°C viscosity of compound modified asphalt is better than that of WPE and WCR modified asphalt. In addition, the waterproofness of compound modified asphalt using waterproofing materials is better than that of common waterproofing materials.